NEW DIRECTIONS IN CRIMINAL LAW THE PRIMACY OF NON-CUSTODIAL PENALTIES AND THE COMPENSATORY FUNCTION - Justyna Fibinger (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2016)
The paper is focused on the consequences of the amendment of the Penal Code provisions relating to the penalties, providing a theoretical background for the problems of penalties considered as a part of the Penal Code as well as indicating the current problems of judicial practice in that respect. Especially, the author focuses on the legislator’s assumptions, namely the introduction of the primacy of non-custodial penalties and the emphasis of the compensatory function of criminal law.